(untitled) (Revista Contexto & Educação, 2024)
This article presents a Systematic Literature Review (SLR) that aimed to know some of the research conducted and published in the form of article on the application and insertion of Augmented Reality (AR) in the context of teaching mathematics. Having as database the CAPES’ Journal Portal, Google Scholar and the SCIELO platform, the SLR highlights fifteen researches carried out in the period from 2012 to 2022 that meet the pre-established criteria. The results reveal that most of the articles are related to the Spatial Geometry topic and that there is a great concern of the researchers with motivation, interest and student satisfaction.